Endovascular Repair of a Chronic AV Fistula Presenting as Post-Partum High Output Heart Failure. (2016) - Kubelik, D.; Morellato, J.; Jetty, P.; Brandys, T.; Hajjar, G.; Hill, A.; Nagpal, S.
Abstract : Introduction: Acute injury to the large vessels is the most feared of diagnoses for a spinal surgeon, but far more common is the delayed presentation of arteriovenous fistula (AVF) formation. The mean time to diagnosis of an AV fistula in this scenario is just over 1 month. Treatment can include both open and endovascular repair. Report: This study presents a case of an otherwise healthy 39-year-old woman who initially presented with orthopnea, leg edema, and a presumptive diagnosis of post-partum cardiomyopathy. Cardiac investigations revealed high output cardiac failure and an abdominal CT scan confirmed an arterial venous fistula from the left common iliac artery to left common iliac vein. The patient maintained a cardiac output three times normal prior to her definitive treatment. This high flow physiology caused unique challenges for the endovascular procedure as the stent graft collapsed and distorted toward the iliac side wall. The AV fistula was eventually covered successfully and post-operative studies show no further fistula and normal cardiac function. This case demonstrates an unanticipated effect of very high flows of stent graft deployment. Discussion: Extreme high flow AV fistulas can present as unexpected challenges to endovascular repair. These issues may be ameliorated by techniques such as controlled hypotension, adenosine, ventricular pacing, or proximal balloon occlusion. Highlights: This chronic AV fistula was diagnosed 12 years after lumbar discectomy. Only after the normal physiological state of pregnancy, and its elevated high cardiac output requirements did the patient decompensate with orthopnea and edema. This otherwise healthy 39-year-old woman had three times the cardiac output expected which was caused by her iliac artery to iliac vein fistula. Endovascular treatment is a viable option to cover the fistula, but the high flows can collapse and distort the stent graft during deployment. Controlled hypotension, adenosine, ventricular pacing or proximal balloon occlusion may be appropriate if extreme flows are anticipated.